Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand - Zhu, Keli; Yao, Zhiyuan; Bai, Xiujuan; Li, Shuqiang (Zootaxa, 2018)
Five new species from four species-groups of the genus Pholcus Walckenaer, 1805 are described from China and Thailand: P. sakaew Yao & Li sp. nov. (Thailand) from the P. bidentatus species-group; P. umphang Yao & Li sp. nov. (Thailand) from the P. halabala species-group; P. ningan Yao & Li sp. nov. (China) from the P. phungiformes species-group; and P. yongshun Yao & Li sp. nov. (China) and P. yuxi Yao & Li sp. nov. (China), both from the P. yichengicus species-group.